Comprehensive Art Module of Waste to Wealth Management through Online Environment Learning - Abd Shukor, Rina; Ishak, Khairul Azuwan; Abd Rahman, Nor Aziyana; Isnin, Aiqa Afiqah; Jie, Xia (Environment-Behaviour Proceedings Journal, 2023)
This paper elaborates on the recycling and upcycling application associated with collecting and selecting discarded materials to bring new value to discarded materials. This model broadens the curriculum concept of recycling and upcycling waste materials, facilitating knowledge, a practical and cognitive skill applied during production. The module applies technical, practical, and innovative processes of the ’Scavenging method’ (waste hunting or collecting) implemented into the home learning curriculum. In conclusion, this module enables us to understand creative conversion practice through Art. The assembled scraps as functional products contribute to a new hybrid ideology of form following function in an online learning environment.